2002
DOI: 10.1207/s15324826an0901_5
|View full text |Cite
|
Sign up to set email alerts
|

A Neuropsychological Perspective of Aprosody: Features, Function, Assessment, and Treatment

Abstract: Aprosodia, the inability to either produce or comprehend the affective components of speech or gesture, is a common occurrence after brain injury. The prosodic components of speech assist in inferring the attitude and emotion of the speaker and are vital in everyday communication. A review of the literature suggests that the left hemisphere is responsible for modulating the linguistic components of prosody (e.g., timing), whereas the right hemisphere is predominantly responsible for modulating the affective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 31 publications
0
10
0
4
Order By: Relevance
“…Not only is acute RH dysfunction better predicted by emotional prosody impairments as compared to neglect (Dara et al, 2014), it can also lead to important breakdowns in communication and relationships. Interpretation and use of prosodic elements are crucial for communicative interactions and for the well-being of speakers and communication partners (Carton, Kessler, & Pape, 1999; Heilman, 2002; Ross, 1997; Trauner, Ballantyne, Friedland, & Chase, 1996; Voeller, 1995; Weintraub & Mesulam, 1983; Wymer, Lindman, & Booksh, 2002). Recognition of prosody is one means to judge emotional tenor, and thus evoke an appropriately empathetic response.…”
Section: Deficits In Affective Prosody After Strokementioning
confidence: 99%
“…Not only is acute RH dysfunction better predicted by emotional prosody impairments as compared to neglect (Dara et al, 2014), it can also lead to important breakdowns in communication and relationships. Interpretation and use of prosodic elements are crucial for communicative interactions and for the well-being of speakers and communication partners (Carton, Kessler, & Pape, 1999; Heilman, 2002; Ross, 1997; Trauner, Ballantyne, Friedland, & Chase, 1996; Voeller, 1995; Weintraub & Mesulam, 1983; Wymer, Lindman, & Booksh, 2002). Recognition of prosody is one means to judge emotional tenor, and thus evoke an appropriately empathetic response.…”
Section: Deficits In Affective Prosody After Strokementioning
confidence: 99%
“…Wildgruber et al [2004] found bilateral activations in the frontal operculum on discrimination tasks for both affective and linguistic prosody; their right-hemisphere activations were located in BA45/46. Much neuropsychological evidence suggests that the right hemisphere may be dominant for production and perception of affective speech prosody [reviewed in Wymer et al, 2002]. Production and perception of vocal fundamental frequency therefore seems mediated, at least in part, by the right frontal operculum/ anterior insula.…”
Section: Neural Signatures Of Stutteringmentioning
confidence: 99%
“…According to this theory, the RH is responsible for processing all emotional information, positive and negative, perceptive and expressive. For example, there is evidence of RH dominance in the comprehension of emotional content in facial expressions and in the processing of prosody, into national and affective information conveyed during speech (Bobes, Martin, Olivares, & Valdez-Sosa, 2000;Bower, Bauer, Coslett, & Heilman, 1993;Ross & Mesulam, 1979;Wymer, Lindman, & Booksh, 2002). This RH dominance for emotion processing is illustrated in Safer and Leventhal's (1977) classic study, in which participants were asked to make a valence judgement for monaurally presented verbal passages differing in affective tone.…”
Section: Introductionmentioning
confidence: 99%